Experimental Study of 3D Micro-CT on Meso-Structure Evolution of Coal Samples with Different Coal Grades under the Action of Temperature. (26th April 2022) - Xie, Jianlin; Zhao, Dong; Li, Pengwei
Abstract : In the three-dimensional micro-CT experiment system, the room temperature is set to 300°C when different coal samples (lignite, anthracite, lean coal and gas coal) are observed for mesoscopic observation. The evolution regularity of mesoscopic structure is analyzed according to the CT scan of coal samples under different temperatures and three sections of scanning images, and by ImageJ image processing software, image processing, and analysis of the characteristics of the profile, the following conclusions are obtained: (1) Coal specimen will have an overall expansion deformation along with the rise of temperature. The sample expansion can be divided into two types: outward expansion and inward expansion. Outward expansion means that the expansion of the skeleton extends outward from the adjacent pores, while inward expansion means that the solid skeleton intrudes into the adjacent pores. When the temperature rises, the outward expansion and inward expansion occur simultaneously. The dominant expansion mode is influenced by the type of coal sample and the temperature value. (2) With the increase of temperature, coal and anthracite coal specimen pore fissure structure shows an expansion tendency before contraction, while gas coal and lean coal show reverse patterns; in addition to the above the reason of the difference vitrinite differences, one must also consider selected specimen original porosity and mechanical physical properties, such as a combination of other factors. (3) In the temperature range of 100–200°C, when the temperature increases at the same rate, lignite porosity increases the most, followed by gas coal, lean coal, and anthracite. (4) There are certain differences in the variation trends of the pixel proportions of the three sections of the coal specimen, and the temperature values of the three curves at the maximum pixel point are also different, which indicates that the expansion of each point in the coal specimen with the change of temperature is not completely synchronous, and the physical and mechanical properties of the sample are heterogeneous.